Morphological variation of the maxillary lateral incisor - Shintaro Kondo; Grant Townsend; Masanobu Matsuno (Elsevier, 2014)
The maxillary lateral incisor is a variable tooth morphologically. This tooth frequently shows reduction in size, and also various alterations in shape, for example, peg-shaped, cone-shaped, barrel-shaped and canine-shaped. The lateral incisor variant can be analyzed by family studies and using twin models, and these approaches have shown that genetic, epigenetic and environmental factors can all contribute to variation in the trait. Discordance of the phenotype in monozygotic twin pairs could be explained by the following two hypotheses: (1) the embryological environment of monochorionic twin pairs who share the same placenta and chorionic membrane during the prenatal period may differ, (2) phenotypic variation may be caused by epigenetic influences. Possible developmental factors are discussed in this review. Recent studies suggest that Msx1, Pax9 and Axin2 genes predispose to lateral incisor agenesis. Tooth reduction and agenesis seem to represent inter-related complex multifactorial traits, influenced by a combination of gene expression and function, environmental interaction and developing timing. Thus, accumulation of large data banks of morphological data is needed to support and clarify ongoing molecular genetic studies of dental development.